Civic Knowledge and Civic Skills as Enabling Conditions for Digital Citizenship: Examining Their Scope and Limits Among Pre-Service Elementary Teachers - David Lailelleru; Octavian Muning Sayeti; Ari Wibowo; Fathurrohman; Ferry Muhamad Firdaus; Ella Kusuma Wardani (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2026)
The rapid expansion of digital technologies has increased the urgency of developing responsible digital citizenship, yet existing studies have predominantly explained digital citizenship from the perspectives of digital literacy and technological competence, with limited attention to the contribution of civic competence. Addressing this gap, this study examined the extent to which civic knowledge and civic skills function as enabling conditions for digital citizenship among pre-service elementary school teachers. A quantitative cross-sectional design was employed involving 56 participants, and the data were analysed using multiple linear regression. The findings indicate that both civic knowledge and civic skills are significantly associated with digital citizenship, with civic skills demonstrating a stronger contribution. However, the model explained only 38.7% of the variance in digital citizenship, suggesting that responsible digital citizenship is shaped not only by civic competence but also by broader contextual factors, including digital literacy, digital self-efficacy, institutional support, technology access, and learning environments. Conceptually, this study advances the literature by positioning civic knowledge and civic skills as enabling conditions rather than deterministic predictors of digital citizenship. Practically, the findings highlight the importance of integrating civic competence with authentic digital learning experiences, including project-based learning, ethical decision-making, critical evaluation of online information, and collaborative digital activities within teacher education programmes. These findings provide a conceptual and practical foundation for strengthening civic education in preparing future elementary school teachers for responsible participation in increasingly complex digital societies.